Empowerment of Farmer Groups through the Utilization of Rice Husk Waste into Environmentally Friendly Particleboard in Cepoko Village, Jombang Regency - Setiawan, Risqi Firdaus; Hafi Idhoh Fitriana, Nisa; Sari Tondang, Ika (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2025)
Cepoko Village, Jombang Regency, is one of the rice production centers that produces large amounts of husk waste. So far, the waste has been burned or discarded, causing environmental problems and failing to provide added value to the community. This service activity aims to empower farmer groups by utilising rice husk waste to produce environmentally friendly board particles. The methods used include problem identification, technical training, production assistance, and participatory evaluation. The production process involves shredding the husk, mixing adhesive materials, pressing, and drying. The results of the activity demonstrate an increase in the community's understanding and technical skills in converting waste into products of economic value. The resulting board particles have the potential to be developed as alternative building materials. This program also has an impact on the growth of environmental awareness and the opening of local, resource-based business opportunities. This activity proves that appropriate technological approaches combined with participatory empowerment can encourage socio-economic transformation at the village level. Contribution to Sustainable Development Goals (SDGs):SDG 8: Decent jobs and economic growthSDG 11: Sustainable cities and settlements